Effect of CaCl2 and ZnCl2 salts on isobaric vapor-liquid equilibrium in separation of the azeotropic mixture of ethanol plus water - Ghuge, Pravin D.; Mali, Nilesh A.; Joshi, Sunil S. (Fluid Phase Equilibria, 2021)
Present work analyzes potential of calcium chloride (CaCl2) and zinc chloride (ZaCl(2)) salts as entrainer for breaking the minimum boiling azeotrope of ethanol and water. Isobaric vapor-liquid equilibrium (VLE) data for the binary systems of water + ethanol and ternary system of water + ethanol + calcium chloride, and water + ethanol + zinc chloride were measured at a constant pressure of 94.5 kPa. The effect of salts on the relative volatility of ethanol to water as well as on the vapor phase mole fractions of ethanol were also studied experimentally. From the experimental results, it is observed that with addition of salts, the azeotropic point of the ethanol and water system can be eliminated. Salting out effects in case of calcium chloride was more than that zinc chloride salt. The results obtained in this work showed that calcium chloride could be a better choice for separation of the water + ethanol azeotrope. Electrolyte nonrandom two-liquid (eNRTL) model was used to correlate the experimental VLE data. The model prediction with the regressed parameters was found in well agreement with the experimental data. The experimental data obtained in this work was found thermodynamically consistent using van Ness test. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Azeotrope; eNRTL; Ethanol; salts; Vapor-liquid equilibrium; Water